The Effectiveness of Career Programme on Career Development at Exploration Stage among Secondary School Students in Dungun, Terengganu, Malaysia - Halit, Abdul Hanid (2007)
The purpose of this study was to determine the effectiveness of career programme on career development at exploration stage among the secondary school students at Dungun, Terengganu. This study was based on Super’s Career Developmental Theory (1971,1990). Six variables were used that were self-knowledge, career information exploration, career planning, educational and vocational exploration, career decision making and job readiness strategy. The research design in this study was the true experimental pre-test post-test control group design. Two instruments were used in this study, that were SIPK and MPK. The validity and reliability of these two instruments were tested. The results showed that the validity of SIPK were .85 and .80, the reliability were .91 and .89. Whereby the validity of MPK were .89 and .84, the reliability were .98 and .93. Thus the validity and reliability of these two instruments were good. The sample of this study consists of 136 form 4 students who were selected through a combination technique of randomised group cluster and simple randomised sampling. They were divided into two groups that were the experimental group (68) and the control group (68). The experimental group had undergone all the activities based on the MPK and not for the control group. The data collected were analysed by two statistical analysis that were descriptive analysis and inferential analysis. The descriptive analysis used were mean, standard deviation and percentage, whereby the inferential analysis used were two dependent samples t-test and two independent samples t-test. The level of significant chose was .05. The descriptive analysis of data showed that the experimental group reported increasing in career development compared to the control group, there was no increase in career development. In the inferential analysis, the result revealed: 1) there was a significant difference between the mean score of pre- test and the post-test in experimental group for all six variables tested. 2) there was no significant difference between the mean score of pre-test and the post- test in control group for all six variables tested. 3) there was a significant difference of the score mean of post-test between the experimental and the control group for all six variables tested. The significant differences occured between the mean score of pre-test and post-test in the experimental group was the result of the effectiveness career programme that had been carried out. Whereas in the control group there was no significant difference occured between the mean score of the pre-test and post-test. Thus, the Super’s Career Development Theory (1971,1990), the measuring instruments SIPK and MPK were suitable to be used for the career development programme in secondary school students. Based on the findings of this study, implications and suggestions were put forward.